COVID-19 - An Opportunity to Redesign Health Policy Thinking - Joachim P. Sturmberg; Peter Tsasis; Laura Hoemeke (Kerman University of Medical Sciences, 2022)
Coronavirus disease 2019 (COVID-19) dramatically unveiled the fragile state of the world's health and social systems - the lack of emergency health crisis preparedness (under-resourced, weak leadership, strategic plans without clear lines of authority), siloed policy frameworks (focus on individual diseases and the lack of integration of health into the whole of societal activity and its impact on individual as well as community well-being and prosperity), and unclear communication (misguided rationale of policies, inconsistent interpretation of data). The net result is fear - about the disease, about risks and survival, and about economic security. We discuss the interdependencies among these domains and their emergent dynamics and emphasise the need for a robust distributed health system and for transparent communication as the basis for trust in the system. We conclude that systems thinking and complexity sciences should inform the redesign of strong health systems urgently to respond to the current health crisis and over time to build healthy, resilient, and productive communities.